SUARA YANG DIBUNGKAM DI SEKOLAH: ANALISIS SOSIAL-KRITIS ATAS TEKANAN TERHADAP GURU DAN SISWA - Alhafizh, Muhammad Rasyad; Nasarani, Kerensa Ruth Rengganis; Brahmantia, Farrell Anugrah; Fitri, Erika Annisa; Harianto, Muhammad Fauzan (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2025)
Freedom of expression for teachers and students is a crucial element in achieving democratic education. However, in practice there are still silenced voices in schools due to various pressures. This research aims to critically analyze the social conditions that pressure teachers and students, limiting their right to speak up. Using a qualitative method, data were gathered through case studies from media reports and relevant literature. The findings reveal forms of voice suppression, including students punished for criticizing school policies and teachers sanctioned for expressing their opinions. Hierarchical culture and a prevailing culture of silence in educational institutions perpetuate this phenomenon, causing school members’ aspirations to be neglected and constructive dialogue stifled. The discussion highlights that silencing contradicts the principles of national education which are supposed to be democratic, as well as laws that guarantee freedom of expression. As recommendations, it is imperative to foster a school climate that is more inclusive, democratic, and safe for constructive criticism. Supportive policies and commitment from all stakeholders are needed so that schools truly become venues for character building that respects the dignity and voice of every educational individual. ABSTRAK Kebebasan berpendapat bagi guru dan siswa merupakan elemen penting dalam mewujudkan pendidikan demokratis. Namun, realitas di lapangan menunjukkan masih adanya suara-suara yang dibungkam di lingkungan sekolah akibat berbagai tekanan. Penelitian ini bertujuan menganalisis secara sosial-kritis fenomena tekanan yang membatasi hak bersuara guru dan siswa. Dengan metode kualitatif, data dikumpulkan melalui studi kasus dari laporan media dan literatur terkait. Temuan mengungkap bentuk-bentuk pembungkaman suara, antara lain siswa yang dihukum karena mengkritik kebijakan sekolah dan guru yang dikenai sanksi saat menyuarakan pendapat. Budaya hierarkis dan budaya diam di institusi pendidikan turut melanggengkan fenomena ini. Akibatnya, aspirasi warga sekolah terabaikan dan potensi dialog konstruktif terhambat. Hasil pembahasan menekankan bahwa pembungkaman tersebut bertentangan dengan prinsip pendidikan nasional yang demokratis serta amanat hukum yang menjamin hak berpendapat. Sebagai rekomendasi, perlu dibangun iklim sekolah yang lebih inklusif, demokratis, dan aman bagi kritik membangun. Dukungan kebijakan dan komitmen semua pihak diperlukan agar sekolah benar-benar menjadi wahana pembentukan karakter yang menghargai martabat dan suara setiap insan pendidikan.